2010
DOI: 10.1002/adfm.201001448
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline LiMn2O4 Nanotubes Synthesized Via Template-Engaged Reaction as Cathodes for High-Power Lithium Ion Batteries

Abstract: measurements indicate that the nanotubes exhibit superior high-rate capabilities and good cycling stability. About 70% of its initial capacity can be retained after 1500 cycles at 5 C rate. Importantly, the tubular nanostructures and the single-crystalline nature of the most LiMn 2 O 4 nanotubes are also well preserved after prolonged charge/discharge cycling at a relatively high current density, indicating good structural stability of the single-crystalline nanotubes during lithium intercalation/deintercalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
203
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(210 citation statements)
references
References 57 publications
5
203
0
Order By: Relevance
“…Coupled with relatively low production costs and appreciable electrochemical performance at high discharge rates and elevated temperatures, LiMn2O4 is touted as a potential driver of future EV/HEV battery packs, notably against favourable LiFePO4 candidates [264]. Recent nanostructured morphologies of note include nanowires [265][266][267], nanorods [268][269][270][271][272], nanotubes [273], nanoparticles [269,[274][275][276] and ordered meso/porous electrodes [277,278]. Okubo et al [275] have demonstrated an important size-effect occurring in LiMn2O4 particles, confirming that bulk particle sizes are unable to achieve complete lithiation (up to Li2Mn2O4), due to their lower surface area.…”
Section: Limnxoymentioning
confidence: 99%
“…Coupled with relatively low production costs and appreciable electrochemical performance at high discharge rates and elevated temperatures, LiMn2O4 is touted as a potential driver of future EV/HEV battery packs, notably against favourable LiFePO4 candidates [264]. Recent nanostructured morphologies of note include nanowires [265][266][267], nanorods [268][269][270][271][272], nanotubes [273], nanoparticles [269,[274][275][276] and ordered meso/porous electrodes [277,278]. Okubo et al [275] have demonstrated an important size-effect occurring in LiMn2O4 particles, confirming that bulk particle sizes are unable to achieve complete lithiation (up to Li2Mn2O4), due to their lower surface area.…”
Section: Limnxoymentioning
confidence: 99%
“…LiFePO 4 is hard to satisfy the requirements of large energy storage systems because of its small tap density and low discharge voltage. Spinel LiMn 2 O 4 is one of the most promising cathode material due to low cost, abundant resources, and nontoxicity [1,2]. However, the spinel LiMn 2 O 4 electrode suffers from a poor cycling behavior and severe capacity fading at elevated temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Two pairs of oxidation current peaks and reduction current peaks for the cathode are distinct, revealing typical characteristics of two-stage reversible-phase transformation of the spinel LiMn 2 O 4 . Two pairs of separated redox peaks show that lithium ions are extracted and inserted from/into the spinel phase by a two-step process [45,46]. Figure 1a shows the cyclic voltammogram of a LiMn 2 O 4 particle in 0.7 M LiNTf 2 in MePrPyrNTf 2 +10 wt% GBL.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%